(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2019)
Lippia origanoides is a honey shrub which has showed hypotensive potential assessed by in vivo studies. The aim of this work is the development of a pharmaceutical formulation composed by an optimized extract obtained from aerial parts of L. origanoides. The quantification of the naringenin marker in the dry extract and tablets developed was performed, as well as the assessment of the oral acute toxicity in rats. The hydroalcoholic extract of L. origanoides was spray-dried with the addition of colloidal silicon dioxide (Lo-HAE/CSD), and then applied in the preparation of eight different lots of tablets. The influence of the diluent (cellulose or babassu mesocarp), the presence of binder, and the percentage of lubricant, as well as organoleptic and physicochemical characteristics were screened. For the quantification of the marker content both in Lo-HAE/CSD and in the tablets, an analytical curve of the naringenin standard was fitted, and the samples were then analyzed in UFLC. The toxicological assessment was performed in female Wistar rats according to the Acute Toxic Class Method from OECD. The developed tablets produced meet acceptable macroscopic characteristics, and the presence of babassu as diluent provided improved physicochemical properties. The best content of Lo-HAE/CSD in the tablet (100.27%) was identified for the lot containing babassu, composed by 1.0% magnesium stearate, without PVP binder in its formulation. Moreover, Lo-HAE/CSD showed no signs of toxicity. Therefore, the babassu mesocarp powder is a promising pharmaceutical excipient for the development of herbal tablets containing the Lippia origanoides extract.